2019
DOI: 10.1016/j.jhin.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Attributable clinical and economic burden of carbapenem-non-susceptible Gram-negative infections in patients hospitalized with complicated urinary tract infections

Abstract: Background: Gram-negative complicated urinary tract infections (cUTIs) can have serious consequences for patients and hospitals. Aim: To examine the clinical and economic burden attributable to Gram-negative carbapenem-non-susceptible (C-NS; resistant/intermediate) infections compared with carbapenem-susceptible (C-S) infections in 78 US hospitals. Methods: All non-duplicate C-NS and C-S urine source isolates were analysed. A subset had principal diagnosis ICD-9-CM codes denoting cUTI. Collection time (<3 vs 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Recently published studies mainly focus on gram-positive bacteria [ 9 ], while only few studies estimated the burden of CRKP, CRPA, and CRAB in terms of mortality, length of stay (LOS), and cost [ 10 , 11 , 12 , 13 , 14 ]. It was reported that patients with CRKP, CRPA, and CRAB infections were associated with higher mortality, longer hospital stay, and higher hospital costs compared with carbapenem susceptible cases [ 9 , 15 , 16 , 17 ]. In addition, hospital costs incurred by colonized patients with CRKP were also high [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently published studies mainly focus on gram-positive bacteria [ 9 ], while only few studies estimated the burden of CRKP, CRPA, and CRAB in terms of mortality, length of stay (LOS), and cost [ 10 , 11 , 12 , 13 , 14 ]. It was reported that patients with CRKP, CRPA, and CRAB infections were associated with higher mortality, longer hospital stay, and higher hospital costs compared with carbapenem susceptible cases [ 9 , 15 , 16 , 17 ]. In addition, hospital costs incurred by colonized patients with CRKP were also high [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study expanded on a recent study that demonstrated an increased clinical and economic burden of complicated UTIs caused by carbapenem-nonsusceptible gram-negative pathogens. 9 To our knowledge, this is the first study to focus on predictor variables in a UTI population with laboratory-confirmed carbapenem-nonsusceptible infections, in contrast to previous studies that have either assessed variables and burden in patients with a variety of infection types [16][17][18] or with UTIs caused by pathogens with unknown carbapenem susceptibility. 22 Our study population included patients who presented to a broad sample of acute-care health care institutions in the US (n=78) where laboratory-confirmed microbiological nonsusceptibility to carbapenems was established in a large number of urine source isolates (>40,000).…”
Section: Demographicsmentioning
confidence: 96%
“…The overall mortality rate was 5.5% (n=79/1439), and the allcause readmission rate was 25.0% (n=340/1360 live discharges). The mean (standard deviation [SD]) LOS was 12 (14) days, and the median (interquartile range [IQR]) was 12 (8)(9)(10)(11)(12)(13)(14) days. The mean (SD) total cost per case was $21,502 ($37,172), and the median (IQR) was $11,231 ($6384-$21,850).…”
Section: Univariate Analysis Of Associated Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing microbiota from O and C gilts, it was found a higher prevalence of Enterobacter and Klebsiella in C animals (p<0.003), both associated with urinary infections in humans (KOKSAL et al, 2019;GOYAL et al, 2019;TABAK et al, 2019).…”
Section: Microbiota Analysismentioning
confidence: 99%